Prevalence, utilization and conservation strategies for non-timber forest products in South western zone of Nigeria (2012)
The study was carried out to investigate the prevalence and utilization of non-timber forest products (NTFPs) plant species in Omo and Shasha Forest Reserves, Southwestern Nigeria. Data were obtained through the use of structured questionnaires administered to households in forest communities. To complement information from the household survey, focus group discussions (FGDs) were also carried out in each of the sampled communities. In-depth interview (IDI) of forestry staff was further used to supplement the information collected. A simple random sampling technique was employed for the study. In Omo Forest Reserve (OFR), a total of seventy five species distributed in forty three families were recorded, while fifty six species in thirty one families were documented in Shasha Forest Reserve (SFR). Local end-uses of NTFPs include food and food supplements, snacks/sweeteners, wrapping leaves, soup and spices, beverages, dental care supplies, washing tools, roofing/construction materials, medicine and traditional rites items. While access to these resources is important to guarantee the socio-economic well being of the forest dwellers and communities, their sustainable management has not been taken seriously by policy makers thereby contributing to reduction of biodiversity and gradual but irretrievable loss of indigenous knowledge on the uses of most species. To ensure the sustainable utilization of NTFPs in these and similar tropical forest environments therefore, a number of conservation approaches are proposed.